O controle interno na administração pública como instrumento de governança e governabilidade na gestão dos municípios paranaenses - Buligon, Diego (2012)
The current economic and social status implies in changes in behavior of the state, especially in how to administer it. In this context, it is essential to understand the tools that have the power to assist in the implementation of the new management model through the prism of governance (the way / the how) related to governability (Power / Share Policies / Legitimacy). Under the modern approach of Administration, the evolution of management is diametrically linked to the development of internal control, which cannot be seen only as a mechanism for investigation of irregularities, although this is one of its functions. Indeed, this paper aims to discuss the importance of internal control as a means of improving public management focused on the realization of the rights and guarantees of citizens (users - shareholders of the State) and legitimacy of the government, highlighting the functions and control structures the municipalities of Paraná and its relation to the processes of accountability presented by the Court of the State. Through research along the controladorias Paraná State counties, combined with analysis of 399 cases of accountability in fiscal year of 2010 as well as the theoretical framework, it was found that the effectiveness of the internal control system impacts on irregularities (restrictions) and caveats (recommendations) observed in the processes analyzed. Moreover, there is shown that the control system is constituted as unquestioned instrument of governance and governability in managing public res.